Veillonella and Streptococcus are associated with aging of the gut microbiota and affect the efficacy of immune checkpoint inhibitors - Hirasawa, Yuya; Isobe, Junya; Hosonuma, Masahiro; Tsurui, Toshiaki; Baba, Yuta; Funayama, Eiji; Tajima, Kohei; Murayama, Masakazu; Narikawa, Yoichiro; Toyoda, Hitoshi; Shida, Midori; Sasaki, Aya; et al. (Frontiers in Immunology, 2025)
IntroductionThe rapid increase in the number of elderly patients with cancer necessitates treatment strategies based on the effects of aging because of drastic side effects of cytotoxic anticancer agents. Immune checkpoint inhibitors (ICIs) are relatively less toxic and can be easily administered to vulnerable and aged patients suffering from cancer. The diversity of gut microbiota and specific bacteria affects the efficacy and safety of ICIs. Therefore, this study aimed to assess the effect of aging on gut microbiota that play crucial roles in determining antitumor efficacy of drugs.MethodsStool samples were collected from 36 aged patients pathologically diagnosed with solid tumors before the start of drug therapy, and gut microbial composition was analyzed using next generation sequencing. The association between gut microbiota and efficacy and safety of ICIs was analyzed.ResultsThe abundance of Veillonella species significantly decreased in patients aged ≥75 years. Additionally, the gut microbiota in the responder group was significantly higher than that in the non-responder group regardless of age. The abundance of Streptococcus species was significantly higher in the responder group than that in the non-responder group.ConclusionsThese gut microbiota changes with aging, and its characteristics are important parameters that also affect the efficacy of ICIs.